SOSIALISASI SENAM BODY COMBAT KEPADA MAHASISWI DAN DOSEN PROGRAM STUDI KEBIDANAN UNIVERSITAS SINGAPERBANGSA KARAWANG - Morel Sangge Sipahutar; Rahmat Wahyu Ramadhan; Setyo Dwi Argha Pramudya; Deden Akbar Izzuddin (KORSAcs: Jurnal Pengabdian Kepada Masyarakat, 2023)
The purpose of this community service is to provide knowledge and theory about gymnastics, especially body combat gymnastics. The activity is carried out once a week at Singaperbangsa Karawang University, midwifery study program, Karawang City, East Jambe Bay with a period of 1 month. The number of participants who took part in this program was 50 people. The methods used by the Service Team in providing (delivering) training materials are: (1) Lectures, (2) Questions and Answers, (3) Demonstrations, and (4) Practices. The outputs of this activity are: 1) Community knowledge about body combat gymnastic skills with good and correct techniques. 2) Exercise skills in the midwifery study program at Singaperbangsa Karawang University will increase motivation to continue exercising. 3) The ability to utilize existing facilities and infrastructure at Singaperbangsa Karawang University that can be used for exercise. 4) As a suggestion, this activity includes: 1) increasing interest in sports for all campus residents and 2) for campus residents to utilize and maintain existing facilities and infrastructure.